Photoluminescence and time resolved photoluminescence properties in as grown ZnO thin films prepared by DC reactive sputtering for optoelectronic devices. (August 2021) - Zaaboub, Z.; Hassen, F.; Chaabane, L.; Maaref, H.
Abstract: Results of steady-state and time-resolved Photoluminescence (PL) measurements performed on ZnO thin films, deposited on (001) p-doped silicon substrate, by DC reactive sputtering technique for different growth times are presented. In all cases, two emission bands are observed. One is an exciton emission band and the second an intense and broad visible emission band. As the growth time increases, the intensity of the exciton emission decreases while that of the visible emission increases. Time-resolved PL (TRPL) measurements at the UV emission peak show a bi-exponential decay behavior. As the growth time increases, the fast and slow decay lifetimes increase together with a decrease of the amplitude ratio (AR) of the slow decay component to the rapid one due to the reduction of the non-radiative pathways when the oxygen deposition time is short. Moreover, slower rise time of the TRPL signal is observed when the growth time increases, proving the increase of the trap states density in the ZnO band gap. These results suggest that the amount of oxygen deposited as reactive gas in DC reactive sputtering technique must be optimized to improve the performance of UV light-emitting applications.